FAKTOR-FAKTOR YANG MEMENGARUHI ANGGOTA ORGANISASI KEPEMUDAAN ALUMNI BUDI MULIA (ALBUM-MEDAN) TERHADAP DONOR DARAH DI PMI MEDAN TAHUN 2012 - mei rodhiah; Linda T Maas; Tukiman Bakti (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2012)
ABSTRACT   Many factor affecting the members of youth organizations Budi Mulia (Album- Medan) to donate blood in medan red cross 2012. The importance of the availabilityof blood is to meet the need for blood transfusions that could occur anytime such as foraccident victims, cesarean section and for patients with blood diseases such as hemophilia and thalassemia. Therefore, it is very important to know what are thefactors that could affect members of youth organization such as ALBUM-Medan todonate their blood. The purpose of this study was aimed to determine the factors that affect members of youth organization ALBUM-Medan to donate blood. The factors were characteristics,sources of information, knowledge, social capital, attitude, reference groups, intentions and actions of members of youth organization ALBUM-Medan to donate blood at Medan Red Cross in 2012. This research used descriptive quantitative. The number of respondents in this study amounted to 62 people with total sampling as the sampling technique, where the respondent was a person who members of youth organizations ALBUM-Medan that register in 2009-2011. The results are presented in frequency distribution table. This is the result of the research, 33,9 % is 18th years old, 59,7% is male. The catagorized of youth’s sources of information is medium or 71,0%. The catagorized of youth’s knowledge is medium or 67,7%. And for the catagorized of the social capital is medium or 50,0%. The attitude of the responden considered good or 88,7%. The intention of the respondents considered good or 67,7% and for the youth’s action considered bad or 88,7%.